PEMANFAATAN SEDIMEN PERAIRAN TERCEMAR SEBAGAI BAHAN LUMPUR AKTIF DALAM PENGOLAHAN LIMBAH CAIR INDUSTRI TAHU - Ni Luh Gede Sudaryati; I Wayan Kasa; I Wayan Budiarsa Suyasa (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science))
Tofu industries are food industries which use a lot of water, both for operational system and as a basic material for production.Tofu industries produce liquid sewage which contains high organic subtances. Liquid sewage of tofu industries is one of the sources ofcontaminants, so that it is needed to have an appropriate waste processing. In order to overcome liquid sewage problem, a wasteprocessing is to reduce and eliminate dangerous materials and pathogenic microorganisms. Biological treatment is the commonest way inhandling the liquid waste from food industries. One of the biological processing that can reduce the contaminants content in liquidindustrial sewage is activated sludge. This activated sludge can also metabolize and break up the contaminants in the sewage and thisprocessing uses sludge.This research was carried out in order to know the growth rate of microbe biomass in activated sludge from 3 types of sludgetaken from the ditches of the tofu industries, the sludge taken from Pesanggaran Slaughterhouse and the sludge taken from Badung Riverwhich were composed into 4 compositions and then were seeded, than tested to get 4 sludge composition in order to reduce COD in tofuindustrial sewage. The parameters used were physical and chemical views. This research was done by measuring the changes in VSSvalue of the four sludge compositions which were seeded and the COD of the four tested sludge compositions.This research used factorial Randomized Completed sampling that consisting of 2 factors and three repetitions, that is the firstfactor was composition sludge and the second one ws incubation period and then were analyzed by using descriptive comprative analysisand uni –variant analysis.The result of this research shown that the best sludge composition used as activated sludge was the sludge composition takenfrom the ditches of tofu industries was 50 %, the sludge taken from Pesanggaran Slaughterhouse was 25% and the sludge taken fromBadung River was 25 % with had VSS of micobe biomass growth of 2265 mg/L and was able to reduce COD of tofu industrial liquidsewage up to 46.645 mg/L.